2019
DOI: 10.1186/s12891-019-2636-7
|View full text |Cite
|
Sign up to set email alerts
|

Is lower tourniquet pressure during total knee arthroplasty effective? A prospective randomized controlled trial

Abstract: Background Higher tourniquet pressures may be associated with an increased risk of complications. We aimed to determine (1) whether a lower tourniquet pressure [systolic blood pressure (SBP) + 120 mmHg] is as effective as conventional tourniquet pressure (SBP + 150 mmHg) in providing a bloodless surgical field and decreasing blood loss, and (2) whether lowering the tourniquet pressure decreases tourniquet-related complications compared to conventional inflation pressure. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
1
22
0
1
Order By: Relevance
“…Several strategies have been used to reduce the risk for transfusion in TKA patients, such as the use of a tourniquet and tranexamic acid [8,9]. Unfortunately, the side effects of these strategies continue to worry orthopedists, and some patients still need blood transfusions.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been used to reduce the risk for transfusion in TKA patients, such as the use of a tourniquet and tranexamic acid [8,9]. Unfortunately, the side effects of these strategies continue to worry orthopedists, and some patients still need blood transfusions.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that pain is an important in uencing factor for patients' satisfaction with surgery. In the trial, the same enhanced recovery after surgery and postoperative rehabilitation training were used in all groups [27,28]. The analysis of the results showed that the visual analogue scale at 1, 3 and 7 d after the second half of tourniquet application was signi cantly greater than that in the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Automatic pneumatic tourniquet (Changzhou yanling co. LTD) was tied to the upper and middle thigh with inflating pressure as the SBP+150 mmHg. 13 Tourniquet was inflated before skin incision and deflated after implant. Then, the incision was closed after safe hemostasis.…”
Section: Anesthesia and Interventionmentioning
confidence: 99%
“…Both NOSI/ nNOS and NOSIII/eNOS are related to the maintenance of adequate micro-vascular blood flow and the regulation of skeletal muscle function. 11 There is evidence that the degree of muscle injury caused by IRI is closely related to the duration of ischemia, 12 tourniquet inflation pressure, 13 and mode. 14 Therefore, surgeons often try to shorten the time of ischemia, reduce the pressure of the tourniquet, and change the method of using tourniquets in order to reduce the IRI of skeletal muscle of the operated limb.…”
Section: Introductionmentioning
confidence: 99%